Carbohydrate binding molecules in malaria pathology. - Brown, A; Higgins, M (2010)
Interactions between parasite-encoded proteins and host carbohydrate molecules are essential at multiple stages in the life cycle of the malaria-causing parasite, Plasmodium falciparum, and these interactions are targets for the development of therapeutics to treat the disease. Here we review recent structural studies of carbohydrate binding modules that mediate recognition events important for cell invasion and cytoadhesion. In particular we focus on the structures of two molecules; the erythrocyte binding antigen, EBA-175 involved in erythrocyte invasion and the VAR2CSA protein that mediates binding of infected erythrocytes to the placenta. These proteins both use Duffy-binding like (DBL) domains, a Plasmodium specific fold, to bind host carbohydrates, but recent results show that they differ significantly in their architectures and modes of ligand recognition.